2014
DOI: 10.1089/jwh.2013.4327
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behaviors and Sexually Transmitted Infections in a Nationally Representative Sample of Women Veterans and Nonveterans

Abstract: Background: Women veterans are a growing population with unique characteristics and documented health disparities. Few studies have examined their sexual behaviors and rates of sexually transmitted infections (STIs), and none have compared women veterans to nonveterans to identify potential sexual health disparities. Methods: We used data from the 1999-2010 National Health and Nutrition Examination Survey, a nationally representative U.S. survey. We compared lifetime sexual history (age at first intercourse, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…While no articles examined the role of rurality in health behaviors, two medium-quality articles addressed utilization (Table 2). One article reported no differences between metropolitan and There were also two included articles 87,89 on sexual orientation both compared Veterans and non-Veterans, using data from national cohorts, included only women, had more than 1000 participants, and were medium quality; one of these examined the role of sexual orientation on mortality and also addressed trauma exposure 89 *Number of participants unclear in one article on rurality 21 non-metropolitan participants in proportion having a Bcheckup^within the prior 2 years. 137 The other article examined associations with total healthcare expenditures and found significant interaction effects between rural residence and a combined Veteran/VHA-user categorical variable (i.e., non-Veteran, Veteran VHA user, and Veteran non-VHA user); the magnitude of interaction effects was not reported.…”
Section: Ruralitymentioning
confidence: 99%
“…While no articles examined the role of rurality in health behaviors, two medium-quality articles addressed utilization (Table 2). One article reported no differences between metropolitan and There were also two included articles 87,89 on sexual orientation both compared Veterans and non-Veterans, using data from national cohorts, included only women, had more than 1000 participants, and were medium quality; one of these examined the role of sexual orientation on mortality and also addressed trauma exposure 89 *Number of participants unclear in one article on rurality 21 non-metropolitan participants in proportion having a Bcheckup^within the prior 2 years. 137 The other article examined associations with total healthcare expenditures and found significant interaction effects between rural residence and a combined Veteran/VHA-user categorical variable (i.e., non-Veteran, Veteran VHA user, and Veteran non-VHA user); the magnitude of interaction effects was not reported.…”
Section: Ruralitymentioning
confidence: 99%
“…35,36 Despite the fact that there are certain health and educational requirements for military service, studies generally have found that women Veterans have a greater burden of health and psychosocial comorbidities compared with their non-Veteran counterparts, many of which are important risk factors for poor pregnancy outcomes. [37][38][39][40][41][42][43][44] In addition to peer-reviewed literature, a VA report titled "Sourcebook: Women Veterans in the Veterans Health Administration" uses VA electronic medical record (EMR) to characterize the health status of women Veteran VA users. 2 â–şTable 1 lists the most common diagnoses identified in the VA EMR among women Veteran VA users of reproductive age.…”
Section: Risks For Adverse Pregnancy Outcomes and Prevention Opportunmentioning
confidence: 99%
“…Women Veterans have higher rates of obesity and overweight, 37 tobacco use, 37,44 and sexually transmitted infections (STIs) 39 compared with their civilian counterparts. â–şAppendix 1 provides a summary of selected studies using national data sources to compare health of women Veterans or women with a military service history to non-Veterans.…”
Section: Medical and Behavioral Factorsmentioning
confidence: 99%
“…28 The potential implications of these findings for cervical abnormalities or cervical cancer risk are unknown. However, adhering to established sexually transmitted infection and cervical cancer screening guidelines further targets research in this area.…”
Section: Sexually Transmitted Infectionsmentioning
confidence: 99%